On the Use of make to vs. make ø in Early English Medical Writing - Calle-Martín, Javier; Romero-Barranco, Jesús (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2015)
Object infinitive constructions are the most frequent type of non-finite complement clauses, in which the object infinitive may occur either marked (a to-infinitive) or unmarked (a bare infinitive). From a historical viewpoint, the bare infinitive is the preferred form in Old English, the number of examples being comparatively small however. This picture changed in Middle English and especially in early Modern English, when the to-infinitive begins to outnumber the bare infinitive in this kind of clause. The verb make, among others, is considered to be an exception to this, as it is observed to accept both variants from Middle English, even though it later progressed towards the final adoption of the bare construction in Present-Day English. Fischer associates this development of make with the introduction of the verb cause into English, which took over the indirect causation formerly expressed by the verb make, the latter “slowly finding itself restricted to the bare infinitive, expressing only direct causation” (1997, 127). The present paper investigates the construction make to vs. make ø in late Middle English and early Modern English medical writing with the following objectives: (a) to analyse the distribution of the marked and the unmarked infinitive with this verb in the period 1350-1700; (b) to classify the phenomenon according to different text types; and (c) to evaluate the contribution of the following factors in the choice of one particular infinitival form: (i) the presence of intervening elements between the verb and the object infinitive; (ii) the size of the object phrase; and (iii) the morphology of the matrix verb. The data used as source of evidence come from the Corpus of Early English Medical Writing. Keywords: bare infinitive; early English medical writing; make; object infinitive constructions; to-infinitive